ANALISIS PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Pada KSP Mekar Surya Karanganyar) - Mustofa, Sahli; Suddin, Alwi; Wardiningsih, Suprihatmi Sri (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2019)
This study aims to analyze (1) the direct effect of compensation and work motivation on job satisfaction, (2) the direct influence between compensation and work motivation and job satisfaction on performance, (3) the indirect effect of work performance and motivation on employee performance through job satisfaction. The population in this study were all KSP Mekar Surya Karanganyar employees. Data collection techniques using questionnaire instruments through testing validity and reliability. Regression requirements test using classical assumption test while hypothesis testing uses alanalysis path, t test, F test and coefficient of determination (R2). The results showed that (1) compensation and motivation had a positive and significant effect on employee job satisfaction with a value of p value of each < 0.05. (2) Compensation and job satisfaction have a positive and significant effect on performance with the value of p value of each < 0.05, but motivation does not have a significant effect on employee performance because the p value is 0.109 > 0.05. (3) job satisfaction is able to mediate the effect of compensation and motivation on employee performance.